2022
DOI: 10.1002/humu.24326
|View full text |Cite
|
Sign up to set email alerts
|

Clinico‐radiological features, molecular spectrum, and identification of prognostic factors in developmental and epileptic encephalopathy due to inosine triphosphate pyrophosphatase (ITPase) deficiency

Abstract: Developmental and epileptic encephalopathy 35 (DEE 35) is a severe neurological condition caused by biallelic variants in ITPA, encoding inosine triphosphate pyrophosphatase, an essential enzyme in purine metabolism. We delineate the genotypic and phenotypic spectrum of DEE 35, analyzing possible predictors for adverse clinical outcomes. We investigated a cohort of 28 new patients and reviewed previously described cases, providing a comprehensive characterization of 40 subjects.Exome sequencing was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Genomic DNA (gDNA) was isolated from blood using a Gentra ® Puregene DNA Purification Kit (Gentra Systems, Inc. Minneapolis, MN, US), according to the manufacturer’s instructions. Whole-exome sequencing (WES) was performed on the patient’s DNA, as described previously ( Aldhalaan et al, 2021 ; Scala et al, 2022 ). To confirm the result, gDNA samples were amplified by PCR using HPRT1-specific primers (forward GTG​AAA​AGG​ACC​CCA​CGA​AG and reverse CAA​ATT​ATG​AGG​TGC​TGG​AAG​GA).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA (gDNA) was isolated from blood using a Gentra ® Puregene DNA Purification Kit (Gentra Systems, Inc. Minneapolis, MN, US), according to the manufacturer’s instructions. Whole-exome sequencing (WES) was performed on the patient’s DNA, as described previously ( Aldhalaan et al, 2021 ; Scala et al, 2022 ). To confirm the result, gDNA samples were amplified by PCR using HPRT1-specific primers (forward GTG​AAA​AGG​ACC​CCA​CGA​AG and reverse CAA​ATT​ATG​AGG​TGC​TGG​AAG​GA).…”
Section: Methodsmentioning
confidence: 99%
“…Identified variants include microdeletions, essential splice site variants, frameshift, nonsense and missense variants (Figure 3). Identified deletions include a homozygous deletion of ITPA Exons 1-5 in one individual likely to produce complete loss-of-function (Scala et al, 2022). Similarly, the essential splice site variants and the frameshift or nonsense variants introducing premature stop codons upstream of the last exon of the gene are likely to completely abrogate gene expression.…”
Section: Clinical Genetics Of Severe Itpase Deficiencymentioning
confidence: 99%
“…All described individuals with severe ITPase deficiency have epilepsy, and this is frequently refractory to treatment (Scala et al, 2022). Age at seizure-onset ranges from 2 days to 7 months, with median age-at-onset of 4 months.…”
Section: Clinical Genetics Of Severe Itpase Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Missense mutations are responsible for the change in the primary structure of the amino acid. In such cases, it is observed that Arg-178 is replaced with cysteine [11,21]. Moreover, a study also showed that ITPase deficiency may lead to refractory epilepsy, microcephaly, and neurodevelopmental disease [22].…”
Section: Infantile Encephalopathymentioning
confidence: 99%